Observational study of financial and non-financial conflicts of interest among the Japanese government advisory board members concerning coronavirus disease 2019. Issue 4 (27th January 2023) - Mamada, Hanano; Murayama, Anju; Ozaki, Akihiko; Hashimoto, Takanao; Saito, Hiroaki; Sawano, Toyoaki; Yamashita, Erika; Bhandari, Divya; Shrestha, Sunil; Tanimoto, Tetsuya
Abstract : This cross-sectional analysis aimed to assess the extent of conflicts of interest among the Japanese government coronavirus disease 2019 (COVID-19) advisory board members and elucidate the accuracy of conflicts of interest (COI) disclosure and management strategies. Using the payment data from all 79 pharmaceutical companies in Japan between 2017 and 2019 and direct research grants from the Japanese government between 2019 and 2020, we evaluated the extent of financial and non-financial COI among all 20 Japanese government COVID-19 advisory board members. The Ethic Committee of the Medical Governance Research Institute approved this study. Japanese government COVID-19 advisory board members were predominantly male (75.0%) and physicians (50.0%). Between 2019 and 2020, 2 members (10.0%) received a total of $819, 244 in government research funding. Another 5 members (25.0%) received $532, 127 in payments, including $276, 722 in personal fees, from 31 pharmaceutical companies between 2017 and 2019. The average value of the pharmaceutical payments was $9155 (standard deviation: $12, 975). Furthermore, neither the Ministry of Health, Labor, and Welfare nor the Japanese Cabinet Secretariat disclosed financial or non-financial COI with industry. Additionally, the government had no policies for managing COI among advisory board members. This study found that the Japanese government COVID-19 advisory board had financial and non-financial COI with pharmaceutical companies and the government. Furthermore, personal communication received as part of this research indicated that there were no rigorous COI management strategies for the COVID-19 advisory board members. Any government must ensure the independence of scientific advisory boards by implementing more rigorous and transparent management strategies that require the declaration and public disclosure of all COI.